BENTONITE-QUARTZ SAND AS THE BACKFILL MATERIALS ON THE RADIOACTIVE WASTE REPOSITORY - Raharjo Raharjo (Universitas Gadjah Mada, 2005)
An investigation of the contribution of quartz sand in the bentonite mixture as the backfill materials on the shallow land burial of radioactive waste has been done. The experiment objective is to determine the effect of quartz sand in a bentonite mixture with bentonite particle sizes of -20+40, -40+60, and -60+80 mesh on the retardation factor and the uranium dispersion in the simulation of uranium migration in the backfill materials. The experiment was carried out by the fixed bed method in the column filled by the bentonite mixture with a bentonite-to-quartz sand weight percent ratio of 0/100, 25/75, 50/50, 75/25, and 100/0 on the water saturated condition flown by uranyl nitrate solution at concentration (Co) of 500 ppm. The concentration of uranium in the effluents in interval 15 minutes represented as Ct was analyzed by spectrophotometer, then using Co and Ct, retardation factor (R) and dispersivity () were determined. The experiment data showed that the bentonite of -60+80 mesh and the quartz sand of -20+40 mesh on bentonite-to-quartz sand with weight percent ratio of 50/50 gave the highest retardation factor and dispersivity of 18.37 and 0.0363 cm, respectively.